Menghidupi Spiritualitas Ekologis: Sebuah Panggilan Kristen di Tengah Krisis Lingkungan Hidup - Simangunsong, Bestian; Aritonang, Hanna Dewi; Tambunan, Mega Intan (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract. Increasingly severe environmental damage to be a global concern. Reducing the environmental carrying capacity for the survival of all creation is a crucial problem. The purpose of this study is to explore the church's responsibility in living out ecological spirituality as an answer to its calling on earth. Ecological spirituality is reconstructed based on David G. Hallman's ideas about the spirituality of the earth community which is encountered with the ecological context in Indonesia, specifically North Sumatra. This study conducted by a qualitative method with an appreciative inquiry approach. The research result showed the importance of living ecological spirituality as a fulfillment of the church's call to care for and preserve the earth as a common home for all creation.Abstrak. Kerusakan lingkungan yang semakin parah menjadi keprihatinan global. Penurunan daya dukung lingkungan terhadap kelangsungan hidup seluruh ciptaan merupakan masalah krusial. Tujuan kajian ini adalah mengeksplorasi tanggung jawab gereja dalam menghidupi spiritualitas ekologis sebagai jawaban atas panggilannya di bumi. Spiritualitas ekologis direkonstruksi berdasarkan gagasan David G. Hallman tentang spiritualitas komunitas bumi yang dipertemukan dengan konteks ekologis di Indonesia, secara khusus Sumatera Utara. Kajian ini menggunakan metode kualitatif dengan pendekatan apresiatif inquiry. Hasil penelitian menunjukkan pentingnya menghidupi spiritualitas ekologis sebagai pemenuhan panggilan gereja dalam merawat dan melestarikan bumi sebagai rumah bersama bagi seluruh ciptaan.